EXPERIMENTAL RESEARCH ON CURING SELF-COMPACTING CONCRETE WITH CURING COMPOUND - Cuong, Nguyen Hung (GEOMATE Journal, 2023)
The article presents the results of an experimental study on curing self-compacting concrete with a curing compound. The experiment was carried out under two natural weather conditions: hot and dry (summer) and hot and humid (autumn), in the Hanoi area. To evaluate the effectiveness of the curing method with a curing compound, three main aspects were studied: plastic shrinkage, water evaporation, and compressive strength of the samples. The experiment was conducted with three methods: (i) using a curing compound, (ii) using water spraying and (iii) no curing. The experiments showed that the sample cured with a curing compound has the smallest plastic shrinkage, corresponding to 0.67mm/m in hot dry conditions and 0.37mm/m in hot humid condition. In addition, the sample cured with a curing compound also has the smallest rate of water evaporation, corresponding to 12.7% and 5.12% in hot and dry, and hot and humid conditions respectively. At the same time, the self-compacting concrete sample cured with a curing compound has the best R28 sample compressive strength value, reaching 101.4% R28tc in hot and dry conditions and 100.9% R28tc in hot and humid conditions. These results, thereby, have proved the effectiveness of the curing method with a curing compound for self-compacting concrete under Vietnamese weather conditions.